Optimizing Legal Protection for Child from Terrorist Perpetrators in Case of Bullying - Adinda Kusumaning Ratri; Slamet Tri Wahyudi; Handar Subhandi Bakhtiar (International Journal of Social Welfare and Family Law, 2025)
The children of terrorism perpetrators are indirect victims of acts of terrorism committed by their parents. They often face stigmatization, discrimination, and bullying within their communities. Under the Child Protection Law, the children of terrorism offenders are categorized as children who are victims of terrorist networks and therefore require special protection. This study aims to identify the ideal concept of legal protection for children of terrorism offenders against acts of bullying. The research method used is normative juridical with a statute approach, comparative approach, and conceptual approach. The findings show that optimizing legal protection for children of terrorism offenders against bullying should focus on both preventive and repressive measures. Preventive actions to protect children of terrorism perpetrators from bullying. Repressive measures include optimizing the roles of the National Counterterrorism Agency (BNPT), relevant ministries, and institutions through coordinated actions to address the needs and protection of children of terrorism perpetrators.